Letter - Fernández-Shaw, Daniel
030-0059-001 SPANISH EMBASSY, COMMERCIAL OFFICE. 21, CAVENDISH SQUARE, LONDON, W. 1. TELEPHONE, LANGHAM 3671. TELEGRAMS: "OFCOMES" LONDON. 16th September 1938. V. Tewson Esq., Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir, Having been called by my Government to Barcelona, I wish to inform you that Mr. Jose da Casa, Agricultural Attaché to this Embassy, will take over the work of Delegate for the Comité Nacional de Ayuda a España during my absence. Mr. da Casa's Office is at this address. I should be greatly obliged if you would send a note of your consignments to Spain, as each one is effected, indicating the nature of the supplies sent, the date of shipment and the person or organization to whom they are addressed. Confirming what I stated in our last interview, please note that my Government desires that all consignments should be addressed as follows: Comité Nacional de Ayuda a España, Para entrega a .....(the person or organization to whom you wish to send the goods.) I thank you in advance for your kind attention to this matter, and trust to hear from you in due course. Yours faithfully, D F Shaw Commercial Attaché to the Spanish Embassy. 292/946/30/59